Efek Moderasi Kepedulian Lingkungan Manajerial Pada Pengaruh Inovasi Produk Hijau Dan Proses Inovasi Hijau Terhadap Kinerja Berkelanjutan Ukm Sektor Makanan Dan Minuman Di Kabupaten Banjarnegara - Bahtiar Efendi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to examine the effect of green product innovation on sustainable performance, the effect of green innovation processes on sustainable performance, and the moderating effect of managerial environmental concern on the relationship between product innovation and green innovation processes and sustainable performance. The valid responses received through a structured questionnaire were from 110 SMEs in the food and beverage sector in Banjarnegara district. MRA analysis was used to validate the hypothesis from the literature review. The results of this study indicate that individual green product innovation variables have a significant influence on sustainable performance variables. Green innovation process variables individually have a significant influence on sustainable performance variables. The managerial environmental concern variable is unable to moderate the relationship between green product innovation and the relationship between green product innovation and sustainable performance. The managerial environmental concern variable positively and significantly moderates the relationship between the green innovation process and sustainable performance. Keywords: Green product innovation, Green innovation process, Managerial environmental concern, Sustainable performance